Antimicrobial and miticide activities of Eucalyptus globulus essential oils obtained from different Argentine regions - Gende, L.; Maggi, M.; van Baren, C.; di Leo, A.; Bandoni, A.; Fritz, R.; Eguaras, M. (Spanish Journal of Agricultural Research, 2010)
The biological activity of Eucalyptus globulus essential oils derived from plant material obtained from different geographic areas was analyzed in in vitro experiments on Paenibacillus larvae, Varroa destructor, and Apis mellifera. The physicochemical properties, composition, antimicrobial, and bioactivity of these essential oils were studied. The bioactivity against P. larvae was analyzed by means of two in vitro techniques (tube dilution and bioautography). Mite and bee lethality were estimated using a complete exposure method test with oils at different concentrations. Essential oils differed in their composition, albeit their similar physicochemical properties. The minimal inhibitory concentrations range for E. globulus essential oil lay between 600-700 µg mL–1 for Mar del Plata and 900-1,200 µg mL–1 for Valle de Conlara essential oils against all P. larvae strains. The bioautography method determined that limonene accounted for the greatest antimicrobial activity with respect to the other compounds. The complete exposure method at 24, 48, and 72 h yielded lower LC50 values for mites exposed to E. globulus essential oils from Conlara. LC50 values for acari after 72 h of treatment with E. globulus from Mar del Plata and Conlara were 47.1 and 11.7 µL capsule–1, respectively; whilst those for bees was > 20 µL capsule–1 for both oils. The E. globulus essential oils tested in this study featured high efficiency against V. destructor, yet their antimicrobial activity against P. larvae proved to be lower, and innocuous to bees. The present experience promotes the use of active compounds for American fouldbrood and Varroosis management.